Grain Size Engineering and Tuning of Magnetic Properties in Ultra-Thin NiMnGa Glass-Coated Microwires: Insights from Annealing Effects - Mohamed Salaheldeen; Valentina Zhukova; Julian Gonzalez; Arcady Zhukov (Crystals)
We studied the influence of annealing on the magnetic properties and microstructure of ultrathin (metallic nucleus diameter ≈ 5 μm, total diameter ≈ 19 μm) Heusler-type NiMnGa glass-coated microwires prepared using the Taylor–Ulitovsky method. The as-prepared NiMnGa microwires exhibit unexpectedly strong magnetic anisotropy, characterized by a coercivity exceeding 3 kOe at room temperature. Furthermore, their Curie temperature (Tc) lies above room temperature. Additionally, a spontaneous exchange bias of approximately 120 Oe is observed in the as-prepared sample at 100 K. Annealing the microwires leads to a decrease in coercivity, spontaneous exchange bias, and Tc values. Notably, the annealing process shifts the Tc of the samples closer to room temperature, making them more suitable for magnetic solid-state refrigeration applications. Moreover, the hysteresis observed in the temperature dependence of magnetization for the samples annealed for 1 h and 2 h, along with the magnetic softening observed at around 260 K, is attributed to a first-order phase transformation. The observed changes are discussed in the context of internal stress relaxation after annealing, the nanocrystalline structure of both the as-prepared and annealed samples, the recrystallization process, and the magnetic ordering of phases identified in the as-prepared sample and those appearing during recrystallization. The glass coating on microwires offers benefits like better flexibility and resistance to damage and corrosion. However, it is important to recognize that this coating can substantially alter the microwires’ magnetic characteristics. Consequently, precise control over the annealing process is vital to obtain the specific martensitic transformation needed.